The migration of the term "civil war" : a social constructivist explanation - Bailie, Lawrence Craig (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2010)
Although the occurrence of wars between states has been in decline, the same cannot be said of conflict within states "“ especially when considering the innumerable 'Civil Wars' said to have occurred since the end of the Cold War. In this context the use of the word 'innumerable' is qualified more by the variance in how 'Civil War' is understood as a concept (leading to different claims as to how many conflicts of this kind may have occurred over a period of time) and less by their large number. Claims regarding the occurrence of 'Civil War' suggest this type of conflict to be the dominant form at least since the end of World War Two. This prevalence in the face of a decline in inter-state warfare has afforded greater interest to 'Civil War' as a topic of inquiry. The understanding that 'Civil Wars' have with time increased in their occurrence and changed in their nature comes under investigation in this thesis and is seen as problematic in that the means by which a phenomenon is measured (i.e. through its nature) must be fixed so as to measure the frequency of that phenomenon. Using Social Constructivism as a theoretical lens of inquiry, sense is made of this understanding and, furthermore, the true meaning behind the claim that 'Civil War' has changed is revealed. The empirical evidence that accompanies this theoretical work exists in the American Civil War of 1861"“1865 and the debate over the conflict in Iraq following the U.S. invasion in 2003. This debate is used as a means by which to bring the contestation over the notion of 'Civil War' to the fore, while a comparison of this conflict with the quintessential American Civil War reveals the migration of the term.
Keywords: Civil Wars; United States -- History -- Civil War, 1861-1865; Iraq -- History -- Civil War, 1991